PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS KOPERASI USAHA KECIL DAN MENENGAH PROVINSI SUMATERA UTARA - Herni Kurnia Wani; Supriadi Supriadi; Ilham Sonata (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine and analyze the effect of emotional intelligence and work stress on employee job satisfaction. This study is a quantitative descriptive study. Data collection techniques were carried out through interviews, questionnaires and documentation studies. The sample in this study was 77 employees. Variables were measured using a Likert scale. Hypothesis testing used multiple linear regression analysis through the F test and t test. The results of the study indicate that partially, emotional intelligence has a positive and significant effect on employee job satisfaction. Work stress has a negative and insignificant effect on employee job satisfaction. Simultaneously, emotional intelligence and work stress have a positive and significant effect on employee job satisfaction at the Cooperatives and Small and Medium Enterprises Service of North Sumatra Province. Emotional intelligence is the most dominant variable influencing employee job satisfaction at the Cooperatives and Small and Medium Enterprises Service of North Sumatra Province.